Implementation of Fiqh Learning in the New Normal Period - Sri Idayatun; Mutadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
This study aims to describe the fiqh learning model during the new normal and the impact of online learning during the new normal. The method used is qualitative, with data sources of people, place and paper. The data analysis used is data reduction, data presentation and conclusion drawing. The results of this research are that during the fiqh learning takes place in the new normal era, it is carried out in 3 (three) ways, namely learning using online media, limited face-to-face learning and learning with assignments. The positive impact in fiqh learning that takes place in the new normal era is the increasing mastery of information technology, being able to learn anytime anywhere as long as there is an internet network, easy to find learning materials. While the negative impact is the unpreparedness of the teacher in operating information technology, the learning motivation of students decreases, and is constrained by the network.